The IRE1α Inhibitor KIRA6 Blocks Leukotriene Biosynthesis in Human Phagocytes - Tang, Xiao; Teder, Tarvi; Samuelsson, Bengt; Haeggström, Jesper Z. (Frontiers in Pharmacology, 2022)
The ER stress and Unfolded Protein Response (UPR) component inositol-requiring enzyme 1α (IRE1α) has been linked to inflammation and lipid mediator production. Here we report that the potent IRE1α inhibitor, KIRA6, blocks leukotriene biosynthesis in human phagocytes activated with lipopolysaccharide (LPS) plus N-formyl-methionyl-leucyl-phenylalanine (fMLP) or thapsigargin (Tg). The inhibition affects both leukotriene B4 (LTB4) and cysteinyl leukotriene (cys-LTs) production at submicromolar concentration. Macrophages made deficient of IRE1α were still sensitive to KIRA6 thus demonstrating that the compound’s effect on leukotriene production is IRE1α-independent. KIRA6 did not exhibit any direct inhibitory effect on key enzymes in the leukotriene pathway, as assessed by phospholipase A2 (PLA2), 5-lipoxygenase (5-LOX), LTA4 hydrolase (LTA4H), and LTC4 synthase (LTC4S) enzyme activity measurements in cell lysates. However, we find that KIRA6 dose-dependently blocks phosphorylation of p38 and ERK, mitogen-activated protein kinases (MAPKs) that have established roles in activating cytosolic PLA2α (cPLA2α) and 5-LOX. The reduction of p38 and ERK phosphorylation is associated with a decrease in cPLA2α phosphorylation and attenuated leukotriene production. Furthermore, KIRA6 inhibits p38 activity, and molecular modelling indicates that it can directly interact with the ATP-binding pocket of p38. This potent and unexpected, non-canonical effect of KIRA6 on p38 and ERK MAPKs and leukotriene biosynthesis may account for some of the immune-modulating properties of this widely used IRE1α inhibitor.